2017
DOI: 10.3390/molecules22101689
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Phytochemistry, Pharmacology, Pharmacokinetics and Toxicology of Geniposide, a Natural Product

Abstract: Iridoid glycosides are natural products occurring widely in many herbal plants. Geniposide (C17H24O10) is a well-known one, present in nearly 40 species belonging to various families, especially the Rubiaceae. Along with this herbal component, dozens of its natural derivatives have also been isolated and characterized by researchers. Furthermore, a large body of pharmacological evidence has proved the various biological activities of geniposide, such as anti-inflammatory, anti-oxidative, anti-diabetic, neuropr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(66 citation statements)
references
References 152 publications
1
64
0
1
Order By: Relevance
“…It was previously shown to inhibit 5-lipoxygenase [33] and the tumor-promoting factor P-glycoprotein [34] and have anti-angiogenic activity [35] and potential antiasthma properties [36]. Additionally, geniposide was shown recently to protect against sepsis-induced myocardial dysfunction by activating AMPKα to suppress myocardial reactive oxygen species (ROS) accumulation [37]. It is present in nearly 40 species belonging to various families, especially the Rubiaceae, among which the most representative are Tinospora capillipes (native to China), Paederia scandens (native to China), Cornus officinalis (native to China, Japan, Korea), Eucommia ulmoides (native to China), Lantana camara (weed native to Mexico, Central America, the Caribbean, and tropical South America), Paratinospora sagittata (present in southern Taiwanese and mainland Chinese disjunction), Artemisia capillaries (Chinese medicinal herb), Plantago asiatica (native to China, Japan, Korea), Rehmannia glutinosa (native to China), Plantago depressa (native to China, Korea, Himalayas), and Gardenia jasminoides (native to Vietnam, Southern China, Korea, Taiwan, Japan, Myanmar, India, and Bangladesh).…”
Section: Resultsmentioning
confidence: 99%
“…It was previously shown to inhibit 5-lipoxygenase [33] and the tumor-promoting factor P-glycoprotein [34] and have anti-angiogenic activity [35] and potential antiasthma properties [36]. Additionally, geniposide was shown recently to protect against sepsis-induced myocardial dysfunction by activating AMPKα to suppress myocardial reactive oxygen species (ROS) accumulation [37]. It is present in nearly 40 species belonging to various families, especially the Rubiaceae, among which the most representative are Tinospora capillipes (native to China), Paederia scandens (native to China), Cornus officinalis (native to China, Japan, Korea), Eucommia ulmoides (native to China), Lantana camara (weed native to Mexico, Central America, the Caribbean, and tropical South America), Paratinospora sagittata (present in southern Taiwanese and mainland Chinese disjunction), Artemisia capillaries (Chinese medicinal herb), Plantago asiatica (native to China, Japan, Korea), Rehmannia glutinosa (native to China), Plantago depressa (native to China, Korea, Himalayas), and Gardenia jasminoides (native to Vietnam, Southern China, Korea, Taiwan, Japan, Myanmar, India, and Bangladesh).…”
Section: Resultsmentioning
confidence: 99%
“…Geniposide is isolated from medicinal herbs for cholestasis such as Gardenia jasminoides Ellis. Geniposide has many beneficial effects including anti‐inflammation and hepatoprotection . It protects against ANIT‐induced cholestasis and d ‐GlaN/LPS hepatotoxicity .…”
Section: Paradoxical Hepatoprotection and Hepatotoxicity With Herbal mentioning
confidence: 99%
“…Geniposide has many beneficial effects including anti-inflammation and hepatoprotection. 102 It protects F I G U R E 4 TRG5 activation by OA could cause both hepatoprotection and hepatotoxicity. A, d-GlaN/LPS-induced liver injury is associated with cholestasis, and low dose of OA (90 mg/kg, po × 4 d) showed hepatoprotection 37 ; B, high dose of OA (1000 μmoles, 451 mg/kg, po × 10 d) produced cholestatic liver injury as showed in arrows 18 ; C, OA (91 mg/kg, sc × 1 d) produced apparent cell proliferation, and mitotic cells are shown in arrows 27 OA Hepatoprotection Hepatotoxicity TGR5 Cell Proliferation…”
Section: Par Adoxic Al Hepatoprotec Tion and Hepatotoxi Cit Y With mentioning
confidence: 99%
“…A previous study revealed that 6,8-di-C-β-d-glucopyranosyl-luteolin (lucenin-2) is weakly or not cytotoxic against five cancer cell lines [28]. Therefore, iridoids might be responsible for the cytotoxic effect on neutrophils, since some of these metabolites have been described as antiproliferative agents [29]. No toxicity study was found in the literature on banana inflorescences; however, previous bioassays have shown that its incorporation in rat diets might modulate serum cholesterol and glucose [8].…”
Section: Discussionmentioning
confidence: 99%